Property, power, and authority in Rus and Latin Europe, ca. 1000-1236 - Mikhailova, Yulia (Assistant professor of history) (Beyond medieval Europe., 2018)
Offers a new perspective on the ""feudal revolution"" by comparing forms of social and political organization in the Kingdom of the Rus and Latin Europe.